Performance of CO2 enrich CNG in direct injection engine - Firmansyah, F. (Institute of Physics Publishing, 2015)
This paper investigates the potential of utilizing the undeveloped natural gas fields in Malaysia with high carbon dioxide (CO2) content ranging from 28 to 87. For this experiment, various CO2 proportions by volume were added to pure natural gas as a way of simulating raw natural gas compositions in these fields. The experimental tests were carried out using a 4-stroke single cylinder spark ignition (SI) direct injection (DI) compressed natural gas (CNG) engine. The tests were carried out at 180o and 300o before top dead centre (BTDC) injection timing at 3000 rpm, to establish the effects on the engine performance. The results show that CO2 is suppressing the combustion of CNG while on the other hand CNG combustion is causing CO2 dissociation shown by decreasing CO2 emission with the increase in CO2 content. Results for 180Â° BTDC injection timing shows higher performance compared to 300Â° BTDC because of two possible reasons, higher volumetric efficiency and higher stratification level. The results also showed the possibility of increasing the CO2 content by injection strategy.